2017
DOI: 10.1186/s12937-017-0289-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclic parenteral nutrition on parenteral-associated liver dysfunction parameters

Abstract: IntroductionOne of the most common complications of parenteral nutrition (PN) is liver dysfunction (LD). Therapeutic approaches for LD include, among others, administering cyclic parenteral nutrition (cPN), allowing some hours for metabolic rest. The purpose of this study was to evaluate the effectiveness of cPN in treating PN-associated LD.Materials and methodsA retrospective observational study was carried out at the Costa del Sol Hospital in Spain between 2013 and 2014. The study involved inpatients ≥18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…68,101 Several guidelines from nutrition societies are established for the prevention and management of IFALD, including frequent monitoring of liver function, cycled feeding, and limiting the dose of soybean oil-based lipid infusions, which can help clinicians in decision-making and can potentially decrease excess mortality. [101][102][103][104] We found that mortality in patients who have SBS secondary to inflammatory bowel disease is relatively lower, which is consistent with reported higher survival rates in this patient population in recent multicenter studies. 105 We found that severe malnutrition also increased the risk of mortality, which highlights the importance of early protein-energy optimization of these patients to decrease this excess mortality risk.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…68,101 Several guidelines from nutrition societies are established for the prevention and management of IFALD, including frequent monitoring of liver function, cycled feeding, and limiting the dose of soybean oil-based lipid infusions, which can help clinicians in decision-making and can potentially decrease excess mortality. [101][102][103][104] We found that mortality in patients who have SBS secondary to inflammatory bowel disease is relatively lower, which is consistent with reported higher survival rates in this patient population in recent multicenter studies. 105 We found that severe malnutrition also increased the risk of mortality, which highlights the importance of early protein-energy optimization of these patients to decrease this excess mortality risk.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the duration of PN, other factors associated with a higher risk of IFALD are shorter length of the remaining bowel, 98 small intestinal bacterial overgrowth, 99,100 and overfeeding of glucose and lipid, 101 as well as underfeeding, which could result in nutrient deficiencies, such as essential fatty‐acid, choline, and vitamin E deficiencies 68,101 . Several guidelines from nutrition societies are established for the prevention and management of IFALD, including frequent monitoring of liver function, cycled feeding, and limiting the dose of soybean oil–based lipid infusions, which can help clinicians in decision‐making and can potentially decrease excess mortality 101–104 . We found that mortality in patients who have SBS secondary to inflammatory bowel disease is relatively lower, which is consistent with reported higher survival rates in this patient population in recent multicenter studies 105 .…”
Section: Discussionmentioning
confidence: 99%
“…AST and ALT, two highly conservative indicators in liver, are commonly located in hepatic cytoplasm and would release into the circulation when hepatocytes necrotize [ 28 30 ]. In order to detect the protective effect of VE and MT on the liver, the activities of the two enzymes in different groups were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Interruption of PN delivery for at least several hours per day, known as cyclic PN, has also been found to decrease cholestasis prevalence and have favorable metabolic effects, despite the risk of hypoglycemia, in patients aged <3 years. ( 55,56 )…”
Section: Therapeutic and Preventative Approachesmentioning
confidence: 99%